Screening of soybean antifungal isoflavones based on targeted metabolomics analysis - Nishbah Mughal; Xiaowen Zhang; Noman Shoaib; Juncai Deng; Jinya Guo; Jing Zhang; Wenyu Yang; Jiang Liu (Food Chemistry: X)
Soybean (Glycine max) is a key crop rich in bioactive compounds, particularly isoflavones, which play a significant role in plant defense against biotic stress like fungal infections. In this study, nine soybean varieties with varying susceptibility to mildew were evaluated. Isoflavone profiles in seeds and pods were analyzed using high-performance liquid chromatography-mass spectrometry (HPLC-MS), and metabolomics analysis via orthogonal signal correction partial least squares discriminant analysis (OSC-PLS-DA) identified differences between mildew-affected and unaffected samples. Results showed organ-specific changes, with isoflavone aglycones increasing in seeds, while malonylglucosides (M-type) varied in pods. β-Glucoside (G-type) and M-type isoflavones were identified as differential metabolites. Antifungal assays revealed that genistin, among six isoflavone glycosides and aglycones tested, had the strongest inhibitory effects on Aspergillus flavus. Additionally, the identification of G-type and M-type isoflavone glycosides underscores the necessity for further investigation into the roles these metabolites play in the overall antifungal activity observed.